Crude oils as ore fluids: An experimental in-situ XAS study of gold partitioning between brine and organic fluid from 25 to 250°C - Crede, L.; Liu, W.; Evans, Katy; Rempel, Kirsten; Testemale, D.; Brugger, J. (Pergamon, 2019)
Organic matter can be associated with mineralization in hydrothermal ore deposits. One hypothesis is that this organic matter represents remnants of organic fluids (crude oils) that were competing with aqueous fluids for metal transport and contributed to metal endowment. We investigated the transport of gold (Au) in model oil compounds (S-free n-dodecane, CH3(CH2)10CH3, DD; and S-bearing 1-dodecanethiol, CH3(CH2)10CH2SH; DDT) from 25 °C to 250 °C using in-situ synchrotron X-ray absorption spectroscopy (XAS) experiments to determine the speciation and the structural properties of gold complexes in the aqueous- and oil-based fluids. For most experiments, DD or DDT were in contact with Au-bearing acidified water, or acidified water plus 10 wt% NaCl (pH25°C = 1.85 in both cases). Gold rapidly partitioned from the aqueous phase into DD and DDT. Below 125 °C, Au(III)Cl is dominant in the DD and the adjacent water with a refined coordination number (CN) of chloride of 4.0(3) and an AuCl bond length of 2.28 Å, consistent with the tetrachloroaurate complex (AuCl4−) being stable in both the aqueous and organic phases. In contrast, Au(III) is rapidly reduced in the presence of DDT and an Au(I) complex dominates in both water and adjacent DDT with a CN of sulfur ∼2.0, suggesting a [RS-Au-SR]− (RS = DDT with deprotonated thiol group) complex with AuS bond lengths ranging from 2.29(1) Å to 2.31(3) Å. In an open system of DDT in contact with water, of which the water and DDT were analyzed separately, AuCl4− was dominant in the water phase, and Au(RS)2− dominant in DDT, possibly due to different equilibration kinetics in the beaker and glassy carbon tube.